Penentuan Kadar Lemak Dan Protein Pada Daging Dan Biji Durian (Durio Zibethinus Murr.) Lokal Di Pasar Brebes - Desi Sri Rejeki; Ery Nourika Alfiraza; Eek Safita (An-Najat, 2024)
One of the tropical fruits that is rich in nutrients such as fat, protein, carbohydrates, vitamins and minerals is durian. Not a few people enjoy durian fruit, because it can be consumed by people of all ages. Consuming too much durian fruit can cause side effects such as high blood pressure, increased cholesterol levels, obesity and digestive system problems. This research aims to determine the fat and protein content in local durian flesh and seeds and compare the fat and protein levels. This research uses the soxhletation method and the biuret method with the help of UV-Vis spectrophotometry. Sample analysis was carried out qualitatively and quantitatively. The resulting fat content in the flesh of the fruit was 13.58% while in the seeds it was 0.39%, meanwhile the protein content produced in the flesh of the fruit was 24.19% and the seeds were 16.5%. It can be concluded that in durian fruit, the protein content in the flesh and fruit is higher than the fat content. The data obtained were analyzed using the One Way Anova test in SPSS which showed that durian flesh and seeds had significantly or significantly different fat and protein levels (p<0.05).